2019
DOI: 10.1039/c8ta11189h
|View full text |Cite
|
Sign up to set email alerts
|

Sea-urchin-like nickel–cobalt phosphide/phosphate composites as advanced battery materials for hybrid supercapacitors

Abstract: Sea-urchin-like bimetallic nickel–cobalt phosphide/phosphate was found to show superior charge storage performance as a battery material for hybrid supercapacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(78 citation statements)
references
References 42 publications
3
75
0
Order By: Relevance
“…31 The crystallized samples show a typical pseudocapacitive behavior that is closely related to that in other works. 49,51 The electrochemical stability of the c-PC@CoPi-CC sample exhibited a $76% capacitance retention, which is signicantly lower than the $95% achieved for the a-PC@CoPi-CC, indicating an obvious kinetic limitation of the crystallized sample. It has been reported that crystalline samples undergo faster structural deformation during the charge/discharge process, leading to poor stability.…”
Section: Resultsmentioning
confidence: 96%
“…31 The crystallized samples show a typical pseudocapacitive behavior that is closely related to that in other works. 49,51 The electrochemical stability of the c-PC@CoPi-CC sample exhibited a $76% capacitance retention, which is signicantly lower than the $95% achieved for the a-PC@CoPi-CC, indicating an obvious kinetic limitation of the crystallized sample. It has been reported that crystalline samples undergo faster structural deformation during the charge/discharge process, leading to poor stability.…”
Section: Resultsmentioning
confidence: 96%
“…The weak peak at 851.4 eV can be attributed to NiP (Figure 2b), which is not completely oxidized under isolation air on account of a dense passivation layer formation. [ 27 ]…”
Section: Resultsmentioning
confidence: 99%
“…Impressively, the fabricated P-ZCS/HC//reduced graphene oxide (RGO) HSC was found to also possess a remarkable energy density of 62.9 W h kg −1 at 800 W kg −1 along with good flexibility and cycling stability. These properties mean the electrode outperforms most previously published phosphide or sulfide electrodes and devices [16,29,30]. This work thus leads to tremendous possibility for synthesizing multivalent, heteroatom-doped metallic sulfides with excellent performance and stable architecture by a universal and low-cost strategy to fulfill the high demands of flexible SCs.…”
Section: Introductionmentioning
confidence: 86%
“…The DOS patterns of ZCS and P-ZCS (Fig. 6b, c, respectively) both exhibited no band gaps at the Fermi level (denoted as E f ), reflecting the metallic features of the two materials [29]. In addition, the P-ZCS delivered a higher DOS at E f , indicating the higher charge-occupied state and enhanced electron mobility [35].…”
Section: Articles Science China Materialsmentioning
confidence: 96%